Muslim Social Movements in Cirebon and the Emergence of National Resistance Movements Against the Dutch Colonial Government in the Early 20th Century Indonesia - Didin Nurul Rosidin; Mila Amalia; Ihsan Sa'dudin; Eka Safitri (Journal of Asian Social Science Research, 2022)
The early twentieth century saw the emergence of Muslim social movements as a new model of resistance against the Dutch colonial rule in Indonesia. This model of the resistance movement was a response to various changes in politics, social and religious culture in the early decades of the 20th century due to dynamics within the Muslim community as well as the new policy of the colonial government. This article studies the emergence of Muslim social movements in Cirebon, West Java, and its impacts on the development of the Muslims’ resistance movement against the Dutch colonial rule in Indonesia. There have not been many studies of Cirebon's role in Islamic social movements in the early 20th century. Therefore, this article, using a historical method, attempts to contribute to this literature by examining social movements carried out by Muslims in Cirebon and their impacts on the emergence of resistance against Dutch colonial rule in Indonesia. The findings show that Cirebon, which was one of the main centres of early Islamic civilization in the Indonesian archipelago, played a prominent role in the emergence of Muslim social movements in early 20th century Indonesia. Various Muslim social organizations emerged in the area such as Sarekat Islam, Persarekatan Ulama, Nahdhatul Ulama, and Muhammadiyah. Although these social-religious organisations had differences or were in tension on various issues, their emergence succeeded in convincing the native people of the importance of a new strategy in their resistance against the long and hegemonic rule of the Dutch colonial government which had ruled the Cirebon region since the late 17th century.